Quantitative and qualitative analysis of hazardous events in the construction sector: causes, classification and implications - Woźniak, Zuzanna; Hoła, Bożena (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
In most countries worldwide, the construction industry is recognized as one of the sectors with an exceptionally high incidence of accidents. The inherent complexity of construction processes, coupled with the variability of implementation conditions, engenders a multitude of disruptions. These disruptions pose a threat to the life and health of construction employees and can give rise to hazardous events, including accidents and near-misses. The research focuses on identifying direct and indirect causes of hazardous events, intending to determine which factors have the greatest impact on their occurrence. A comprehensive dataset was systematically analyzed, comprising 754 recorded accidents at work (A) and 1717 near-miss events (NM). The research was conducted based on a model of the course of a hazardous event that was developed for the purposes of this study. A categorization system was devised, encompassing eight categories of direct causes and 12 categories of indirect causes. The significance of causes was assessed through the utilization of Pareto-Lorenz analysis and ABC methodology. The most significant factors contributing to occupational accidents were identified: inadequate work organization, improper use of materials by employees, and failure to adhere to instructions. The most significant factors contributing to the occurrence of near misses were identified: improper use of material by an employee, inadequate organization of the workstation, and failure to adhere to instructions.